2009
DOI: 10.1007/s11136-009-9461-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of patients with irritable bowel syndrome in Korea

Abstract: IBS-related symptoms had a great effect on the HRQOL of Korean patients. These results and the considerable prevalence of IBS in Korea indicate that IBS has a substantial social impact in this country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 34 publications
9
63
0
1
Order By: Relevance
“…We speculate that alcohol can increase intestinal membrane permeability and visceral sensitivity, thus changing the normal physiological function of the gut. Our findings that there were no statistically significant differences in QOL and SCL-90-R scores between IBS subtypes are consistent with the results of other previous research (Katsinelos et al, 2009;Park et al, 2009;Jamali et al, 2012). However, Eriksson et al (2008) found that QOL was lower in IBS-C and IBS-M when compared with other subtypes, and showed that the mean psychosocial scores were higher in IBS-M and IBS-C compared with IBS-D.…”
Section: Discussionsupporting
confidence: 92%
“…We speculate that alcohol can increase intestinal membrane permeability and visceral sensitivity, thus changing the normal physiological function of the gut. Our findings that there were no statistically significant differences in QOL and SCL-90-R scores between IBS subtypes are consistent with the results of other previous research (Katsinelos et al, 2009;Park et al, 2009;Jamali et al, 2012). However, Eriksson et al (2008) found that QOL was lower in IBS-C and IBS-M when compared with other subtypes, and showed that the mean psychosocial scores were higher in IBS-M and IBS-C compared with IBS-D.…”
Section: Discussionsupporting
confidence: 92%
“…This produces a cycle that begins with the visceral event and continues to exacerbate feelings of symptom anxiety, which again increases the presence of these events. This could explain why it is common to find low scores in the “Health Worry” domain in several studies [22,28,55,56]. Even after a visit to the doctor, thoughts of a wrong diagnosis or fear of a worse condition may persist [51,57].…”
Section: Discussionmentioning
confidence: 99%
“…Higher scores indicate better HR-QOL [21]. Chosen cutoff values were 80 points or more, indicating no association between the domain and intestinal problems, and less than 65 points, corresponding to moderate to severe IBS [22]. A difference of 14 points was considered clinically significant [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IBS lowers health-related quality of life of the patient as well as gastroesophageal reflux disease, diabetes mellitus and depression [2]. It is prevalent irrespective of race [3][4][5]. IBS is defined as recurrent abdominal pain or discomfort at least 3 days per month in the last 3 months associated with two or more of the following: improvement of symptoms with defecation, onset associated with a change in frequency of stool, and/or onset associated with a change in form (appearance) of stool [6].…”
Section: Introductionmentioning
confidence: 99%